Indoor radon exposure and lung cancer: a review of ecological studies. Issue 1 (December 2016) - Yoon, Ji; Lee, Jung-Dong; Joo, So; Kang, Dae
Abstract Lung cancer has high mortality and incidence rates. The leading causes of lung cancer are smoking and radon exposure. Indeed, the World Health Organization (WHO) has categorized radon as a carcinogenic substance causing lung cancer. Radon is a natural, radioactive substance; it is an inert gas that mainly exists in soil or rock. The gas decays into radioactive particles called radon progeny that can enter the human body through breathing. Upon entering the body, these radioactive elements release α-rays that affect lung tissue, causing lung cancer upon long-term exposure thereto. Epidemiological studies first outlined a high correlation between the incidence rate of lung cancer and exposure to radon progeny among miners in Europe. Thereafter, data and research on radon exposure and lung cancer incidence in homes have continued to accumulate. Many international studies have reported increases in the risk ratio of lung cancer when indoor radon concentrations inside the home are high. Although research into indoor radon concentrations and lung cancer incidence is actively conducted throughout North America and Europe, similar research is lacking in Korea. Recently, however, studies have begun to accumulate and report important data on indoor radon concentrations across the nation. In this study, we aimed to review domestic and foreign research into indoor radon concentrations and to outline correlations between indoor radon concentrations in homes and lung cancer incidence, as reported in ecological studies thereof. Herein, we noted large differences in radon concentrations between and within individual countries. For Korea, we observed tremendous differences in indoor radon concentrations according to region and year of study, even within the same region. In correlation analysis, lung cancer incidence was not found to be higher in areas with high indoor radon concentrations in Korea. Through our review, we identified a need to implement a greater variety of statistical analyses in research on indoor radon concentrations and lung cancer incidence. Also, we suggest that cohort research or patient-control group research into radon exposure and lung cancer incidence that considers smoking and other factors is warranted.